Destruction of the cell membrane and inhibition of cell phosphatidic acid biosynthesis in Staphylococcus aureus: an explanation for the antibacterial mechanism of morusin. Issue 10 (16th September 2019) - Pang, Daorui; Liao, Sentai; Wang, Weifei; Mu, Lixia; Li, Erna; Shen, Weizhi; Liu, Fan; Zou, Yuxiao
Abstract : Morusin from mulberry inhibits the growth of S. aureus by destroying its cell membrane and further moderating the phosphatidic acid biosynthesis pathway. Abstract : Morusin is a prenylated flavonoid found in mulberry that shows antimicrobial activity against foodborne pathogens. The MIC values of morusin toward S. aureus ATCC 6538 and S. aureus ATCC 25923 were both 14.9 μmol L −1 . This study further investigated the antimicrobial mechanism of morusin in inhibiting the growth of Staphylococcus aureus ATCC 6538. Scanning electron microscopy and transmission electron microscopy revealed that morusin disrupted the integrity of the bacterial cell membrane. Morusin may also affect the phospholipid-repair system of bacteria, which repairs membrane structures. To test this hypothesis, quantitative real-time PCR was used to examine the effect of morusin treatment of S. aureus on the regulation of genes associated with the cell phosphatidic acid biosynthesis pathway. Gas chromatography–mass spectrometry was used to investigate the fatty acid components, which are used to synthesize bacterial phosphatidic acids. In summary, the results revealed that morusin showed a potent antibacterial effect by disrupting the cell membrane architecture and inhibiting the phosphatidic acid biosynthesis pathway of S. aureus .